Pendampingan Pendampingan Anak Didik Lembaga Pembinaan Khusus Anak (LPKA) II Bandung dalam Pengembangan Produk Sabun - Amalia, Anisa; Khaira Nursal, Fith; Ridwan Zamzany, Faizal; Nining, Nining (Jurnal SOLMA, 2023)
Background: Skill development is an activity that can be provided by LPKA officers and from the wider community, such as educational institutions. One of the trainings from the Community Partnership Program (PKM) that can be taught to LPKA Students is the manufacture of household soap and efforts and strategies to market it as a home product that is not inferior in quality to industrial products. This training is expected to increase the skills of students in producing quality soap products and improve the ability of students to do marketing so that they can be used as provisions for students when returning to society. Method: Students of LPKA II Bandung as non-productive community partners are targets that have the potential to develop their skills so as to reduce the burden on the government in overcoming employment problems. The program stages consist of training in making household soap products in the form of liquid dish soap and solid soap using natural materials that are easily obtained. Indicators of success from providing this material can be known by comparing the value of test results before and after the activities obtained by participants. Results: There was a significant increase in participants' knowledge about the quality and quality of soap and product marketing techniques (p < 0.05). Conclusion: There was a significant increase in participants' knowledge about the quality and quality of soap and product marketing techniques (p < 0.05).